The Influence Of Post Traumatic Experience On The Personality Development Of Lisbeth Salander In Stieg Larrson's The Girl With The Dragon Tattoo Novel (2008): A Psychoanalytic Criticism - Sari, Efiyanti Puspita, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S. M. Hum (2014)
The major issue of this study is How the influence of past traumatic experience on the personality development of Lisbeth Salander is reflected in Stieg Larsson's The Girl with the Dragon Tattoo novel. The objective of this study is to identify what causes the influence of past traumatic experience on the personality development in the self of Lisbeth Salander and to explain way Lisbeth Salander tries to solve the problem of past traumatic experience on the personality development.The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. Primary data is The primary data sources are taken from Stieg Larsson's novel The Girl with the Dragon Tattoo and the secondary data sources are taken from literary books or any information related to past traumatic experience on the personality development that support the psychoanalytic criticism. The data analysis method is descriptive qualitative analysis based on psychoanalytic criticism. The result of the study is a follows. First, based on the structural analysis, it can be concluded that in this novel the author conveys a moral message that "One cannot escape from one's past time". Secondly, according to psychoanalytic analysis it can be concluded that in this novel the author illustrates a psychological phenomenon in which an individual is very much influencedby the past traumatic experience.